Penerapan Relaksasi Benson Untuk Menurunkan Fatigue Pada Pasien Coronary Artery Disease RSUD Dr. Moewardi Surakarta - Dian Okviana Putri; Hermawati Hermawati; Rosma Karinna Haq (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background; Coronary Artery Disease (CAD) contributes 31% of deaths, mostly in the form of coronary heart disease (CHD) and cerebrovascular accidents. One of the main symptoms in CAD patients is fatigue during the recovery period after a heart attack and during cardiac rehabilitation. One of the non-pharmacological therapies to reduce fatigue is Benson's relaxation therapy. Benson relaxation is a breathing relaxation technique that is combined with involving the patient's belief factor, namely through soothing words according to the adherents. Objective: To find out the results of the implementation regarding the administration of Benson relaxation therapy to reduce fatigue levels in CAD patients. Methods: Using a case study design, respondents to 2 patients treated at RSUD dr. Moewardi Surakarta. Measuring tool for fatigue using the Maastricht Questionnaire (MQ). The level of fatigue before the benson therapy was carried out, the two respondents were different. Respondent 2 has a higher level of fatigue, namely 27 (moderate) compared to respondent 1 16 (mild). Results ; There was a change in the level of fatigue between before and after being given benson relaxation in 2 respondents with CAD who were treated at the Aster 5 Ward of Dr. Moewardi Hospital Surakarta.